FACTORS AFFECTING THE DEMAND OF LABOR IN THE 10 REGENCIES/CITIES OF THE SUMATERA UTARA PROVINCE - Rahmad Cahyadi (LPPM Universitas Malikussaleh, 2021)
This study aims to determine the factors that affect the demand for labor in Sumatera Utara Province. This study discusses panel data analysis using data on labor demand, output, number of companies, and economic growth in Sumatera Utara Province from 2013-2019. The regression data panel can be estimated using three models, namely the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM). To get the best model, two tests were used, namely the Chow test and the Hausman test. In this study, the best model is obtained is the Fixed Effect Model. Estimation of parameters in panel data regression with Fixed Effect Model obtained a mathematical equation, namely LDit = 3940.726 + 1.60.10-10Oit + 67.06560JPit + 146.0139Git + eit. Based on the significance test, the demand for labor is simultaneously influenced by output, the number of firms and economic growth. When viewed by a partial test (t test), the output variable and the number of companies have a positive and significant effect on labor demand. Meanwhile, the economic growth variable has a positive but insignificant effect on labor demand. Estimation of parameters in panel data regression with Fixed Effect Model obtained a mathematical equation, namely LDit = 3940.726 + 1.60.10-10Oit + 67.06560JPit + 146.0139Git + eit. Based on the significance test, the demand for labor is simultaneously influenced by output, the number of firms and economic growth. When viewed by a partial test (t test), the output variable and the number of companies have a positive and significant effect on labor demand. Meanwhile, the economic growth variable has a positive but insignificant effect on labor demand. Estimation of parameters in panel data regression with Fixed Effect Model obtained a mathematical equation, namely LDit = 3940.726 + 1.60.10-10Oit + 67.06560JPit + 146.0139Git + eit. Based on the significance test, the demand for labor is simultaneously influenced by output, the number of firms and economic growth. When viewed by a partial test (t test), the output variable and the number of companies have a positive and significant effect on labor demand. Meanwhile, the economic growth variable has a positive but insignificant effect on labor demand. the output variable and the number of companies have a positive and significant effect on labor demand. Meanwhile, the economic growth variable has a positive but insignificant effect on labor demand. the output variable and the number of companies have a positive and significant effect on labor demand. Meanwhile, the economic growth variable has a positive but insignificant effect on labor demand.